The efficacy and safety of Xueshuantong (lyophilized) for injection in the treatment of unstable angina pectoris: A systematic review and meta-analysis - Xi, Junyu; Wei, Ruili; Cui, Xin; Liu, Yi; Xie, Yanming (Frontiers in Pharmacology, 2023)
Xueshuantong (lyophilized) for injection (XST) is an effective herbal medicine for the treatment of Unstable Angina Pectoris (UAP). However, a meta-analysis of XST combined with Conventional Treatments (CTs) for UAP remains to be explored. The purpose of this study was to investigate the effectiveness and safety of XST combined with CTs in the treatment of patients with UAP. Data were retrieved from the Cochrane Library, PubMed, Web of Science, Embase, CNKI, VIP, Wanfang, and CBM databases. A meta-analysis was performed using revman5.4 and stata16.0, and the quality of the included literature was evaluated according to Cochrane Evaluation Manual 5.1. The GRADE assessment was performed by the GRADEprofiler3.6. The trial sequential analysis was performed using TSA0.9. A total of 34 studies involving 3518 patients were included.In summary. The available literature data and systematic evaluation methods demonstrate that XST combined with CTs improves the therapeutic effect of UPA, relieves angina symptoms, and improves hematologic parameters compared with CTs alone. No serious adverse effects were observed in this study, and the addition of XST to CTs is conditionally recommended. However, a more rigorous RCT should be designed and completed before widespread recommendation.